Grandparent-Grandchild Relationships, Generativity, Subjective Well-Being and Self-Rated Health of Older People in Chile - Elgueta-Rosas, R (Elsevier Ltd, 2022)
With increasing life expectancy, grandparents and grandchildren have more years available to share. Furthermore, with lower fertility rates and fewer grandchildren, relationships can be more frequent and profound. Intergenerational relationships are expected to be associated with older people s quality of life, especially in Latin American countries such as Chile, with high intergenerational co-residence and contact between generations. This research aims to analyze the associations between the characteristics of intergenerational relationships and grandparents subjective well-being (Diener Scale and Satisfaction) and self-rated health. The novelty stems from including the structural characteristics of relationships with grandchildren (frequency of contact, closeness, and care), the activities they share (generativity), and the quality of relationships (ambivalence). This study is based on data from a specific face-to-face grandparenting survey conducted on a sample of 464 grandparents in January 2020. It is representative of older Chilean grandparents living in private dwellings. Multiple logistic and ordinary regression models were estimated using the Diener Scale, unique satisfaction question, and health self-perception. The results demonstrated that subjective well-being, but not self-rated health, was highly associated with the characteristics of intergenerational relationships, especially with the quality of relationships and with generative activities such as recreational activities and family identity. In conclusion, intergenerational relationships quality and content are strongly associated with subjective well-being in old age, but not with health self-perception. Even in a Latin American country like Chile, with high co-residence and intergenerational contact, the variations in quality and generativity activities significantly explain the variations in subjective well-being. For this reason, policies for the promotion of well-being in older people must consider the family environment in which older people live, encompassing wider family networks, including grandchildren. © 2022